Mechanism of Anti-Inflammatory Drugs in the Early Treatment of Oral Gingival Mucosa and Soft Tissue Trauma. (29th September 2022) - Zhu, Yanfeng; Lin, Fei; Chen, Weihui
Abstract : Traumatic tissue develops an uncontrolled inflammatory response that causes secondary damage to the injured tissue and other parts of the body. Therefore, preventing wound infection, reducing inflammatory response, and reducing secondary tissue damage are the keys to early treatment of tissue trauma. In the treatment of gingival soft tissue trauma, anti-inflammatory and analgesic drugs are reasonably selected according to the condition, which can effectively reduce inflammation, and they help periodontal tissue regeneration and healing. However, there are few studies on the mechanism of anti-inflammatory drugs in the early treatment of oral gingival mucosal soft tissue trauma, and the specific mechanism is unknown. Therefore, this paper explored the mechanism of anti-inflammatory drugs in the early treatment of oral gingival mucosa and soft tissue trauma through experiments, which provided theoretical support for the clinical treatment of gingival mucosa and soft tissue trauma repair. In this paper, two anti-inflammatory drugs, levofloxacin and metronidazole, were selected to measure their release properties in vitro and in vivo . Then, the white-eared rabbits were treated with gingival wound treatment experiments, and the physiological characteristics, intratissue pressure, tissue partial pressure of oxygen, IL-6 content, and PGE2 content were determined at each postinjury period, and the mechanism of action of anti-inflammatory drugs was determined. Research results have shown that anti-inflammatory drugs can significantly inhibit the content of IL-6 and PGE2 in gingival soft tissue after injury, reduce the local inflammatory response, and accelerate tissue healing.